Echinococcosis Mimicking Autoimmune or Malignant Bile Duct Disease - Goetz, M.; Hainz, M.; Schadmand-Fischer, S.; Kittner, J. M.; Heinrich, S. (Zeitschrift für Gastroenterologie, 2013)
Indeterminate strictures of the bile ducts are common diagnostic dilemmas in gastroenterology, and differential diagnosis includes inflammatory and neoplastic diseases. Alveolar echinococcosis (AE) is rarely considered as a differential diagnosis, although it is endemic in the Northern hemisphere. In this case report on a 50-year-old male patient, the lack of cystic lesions or calcifications on CT, and suggestive ERCP findings made a hilar cholangiocellular carcinoma the most probable differential diagnosis, and only explorative laparotomy provided the definite diagnosis of AE. AE should therefore be included in the differential diagnosis of indeterminate biliary strictures even in the absence of typical stigmata in imaging studies.
Keywords: echinococcosis; bile duct cancer; autoimmune cholangitis